The effect of soy flour on cookie quality - Petrović Jovana; Pajin Biljana; Šereš Zita; Lončarević Ivana; Fišteš Aleksandar; Šubarić Drago; Zarić Danica (2016)
Cookies are a popular confectionery product with a unique texture and taste, long shelf life and a relatively cheap price; therefore, it is a widespread snack among people of all generations. Nevertheless, cookies are usually made of wheat flour and most formulations are highly caloric and have a low fiber content. Soy flour is an excellent source of proteins, fibers, vitamins and minerals and it is being considered as a great supplement to wheat flour because it increases nutritive characteristics of the final product. By their digestibility and amino acid content, soy proteins are very similar to proteins derived from animals. They also contain many essential amino acids, which are deficient in most of the cereals. The purpose of this work was to determine the effect of soy flour on quality of cookies. Wheat flour was supplemented with 35% of soy flour (full-fat toasted, low-fat toasted, defatted lightly toasted, toasted and soy protein concentrate). The supplementation of wheat flour with soy flour had affected nutritive value and sensory characteristics of cookies.